Safety, Immunogenicity, and Efficacy of a Recombinant Vesicular Stomatitis Virus Vectored Vaccine Against Severe Fever with Thrombocytopenia Syndrome Virus and Heartland Bandavirus - Philip Hicks; Tomaz B. Manzoni; Jonna B. Westover; Raegan J. Petch; Brianne Roper; Brian B. Gowen; Paul Bates (Vaccines)
Background: Severe fever with thrombocytopenia syndrome virus (SFTSV) is a recently emerged tickborne virus in east Asia with over 18,000 confirmed cases. With a high case fatality ratio, SFTSV has been designated a high priority pathogen by the WHO and the NIAID. Despite this, there are currently no approved therapies or vaccines to treat or prevent SFTS. Vesicular stomatitis virus (VSV) represents an FDA-approved vaccine platform that has been considered for numerous viruses due to its low sero-prevalence in humans, ease in genetic manipulation, and promiscuity in incorporating foreign glycoproteins into its virions. Methods: In this study, we developed a recombinant VSV (rVSV) expressing the SFTSV glycoproteins Gn/Gc (rVSV-SFTSV) and assessed its safety, immunogenicity, and efficacy in C57BL/6, Ifnar−/−, and AG129 mice. Results: We demonstrate that rVSV-SFTSV is safe when given to immunocompromised animals and is not neuropathogenic when injected intracranially into young immunocompetent mice. Immunization of wild type (C57BL/6) and Ifnar−/− mice with rVSV-SFTSV resulted in high levels of neutralizing antibodies and protection in a lethal SFTSV challenge model. Additionally, passive transfer of sera from immunized Ifnar−/− mice into naïve animals was protective when given pre- or post-exposure. Finally, we demonstrate that immunization with rVSV-SFTSV cross protects AG129 mice against challenge with the closely related Heartland bandavirus despite negligible neutralizing titers to the virus. Conclusions: Taken together, these data suggest that rVSV-SFTSV is a promising vaccine candidate for SFTSV and Heartland bandavirus with a favorable safety profile.